A Stepwise Risk Assessment for Explosion Events considering Probability Distribution of Explosion Load Parameters. (7th November 2018) - Kang, Ki-Yeob; Wang, Xiangyu
Abstract : The potential risk of explosion always exists in offshore topside facilities that deal with flammable materials. Thus, explosion risk analysis taking into account possible scenarios should be performed during the design process to reduce probability of such terrible accidents. There are several technical documents for explosion risk analysis. The analysis usually includes performance criteria, risk acceptance range, and corresponding explosion design load taking into account explosion pressure. However, this standard procedure is not sufficient to assess the potential risk of explosion, since it is usually based solely on the severity of overpressure. Therefore, more in-depth analysis is required to understand the potential risk taking explosion wave profiles into account. In the present paper, a stepwise analysis of gas explosion risk elements has been performed. Quantitative and qualitative analyses of explosion risk have been performed based on the framework of typical explosion risk analysis methods. In addition, both the probability distribution of explosion load parameters taking into account overpressure and its impulse and their correlation have been investigated extensively.